The Effects of the Court’s Patronage on the Selection of Books for Translation in the State Translation Bureau - Bolouri, Mazdak; Mirkiaei, Mehdi (Iranian Journal of Translation Studies, 2019)
This study explored the works translated in the State Translation Bureau at the time Nasser al-Din Shah Ghajar ruled in Iran. The aim was to explore the Court’s role in the selection of books for translation. To do so, libraries and online data banks were searched to prepare the list of books translated in the Bureau, and then, within the framework of Lefevere’s Patronage Theory, the Shah’s support for the translation of certain works and his negligence for certain other works were analyzed. The works on the list were categorized into travel writing, newspaper articles, history, literature, politics, geography, science, military texts, economy and others. The Shah’s interests and the need he felt for the translation of certain works as well as attempts made by the chairman of the Bureau to inform the Shah were found to be the most important factors influencing the selection of works for translation. The largest number of translated books belonged to the categories of travel writing, newspaper articles and history. In addition, books of literature, politics, geography, science and military tactics were also translated considerably. However, few books were translated in areas such as economy and agriculture, and no books were selected for translation in those areas for which the Shah felt no need, or which he opposed seriously. The non-selection of works was evaluated as relevant to the Shah’s unwillingness for reform and changes in the status quo.